Effect of Lactobacillus casei and yogurt administration on prevention of Pseudomonas aeruginosa infection in young mice - Alvarez, Gladis Susana (2001)
Pseudomonas aeruginosa is an opportunistic pathogen that rarely causes pulmonary disease in normal hosts but one that is an important cause of acute pneumonia in immunocompromised patients, including neonates, and of chronic pneumonia in patients with cystic fibrosis. The aim of this work was to study the effect of oral administration of Lactobacillus casei and yogurt on prevention of P. aeruginosa lung infection in young mice (3 weeks old). This study demonstrates that oral administration of L. casei or yogurt to young mice enhanced lung clearance of P. aeruginosa and phagocytic activity of alveolar macrophages through a dose-dependent effect. There were, however, no significant differences in white blood cell (WBC) differential counts. Furthermore, it was observed that previous administration of L. casei or yogurt induced a significant increase in IgA and IgM levels in bronchoalveolar lavages (BALs) after a P. aeruginosa infection, although there was no relationship with the serum values.